Segregation of an X ring chromosome in two generations. Issue 4 (August 1980) - Dallapiccola, B; Bruni, L; Boscherini, B; Pasquino, A M; Chessa, L; Vignetti, P
Abstract : A 45, X/46, X, r(X) mosaicism was found in a mother and daughter. Characterisation of the ring by banding studies showed that breakpoints had occurred at bands Xp13 and Xq27. It is confirmed that women heterozygotes for partial deficiencies of the short arm of an X chromosome are fertile. Although the mother developed secondary amenorrhoea at the age of 29, it is suggested that fertility per se may not be affected by deficiencies of the distal part of Xq.